Determinants of Quality Improvement in Banking Service Through Customer Loyalty Approach - Forouhandeh, Behnam (2010)
The aim of this research was to examining the determinants of quality improvement in banking service through customer loyalty approach. The significance of this research is intended to help the bank\'s managers to identify the determinants of quality of the services that offer by the bank based on the customer satisfaction experience and consequently regarding to the loyalty intention approach.